Investigating Solutions for Social and Human Factors in Requirements Engineering - Vieira Junior, Cassiano Medeiros; Gonçalves, Rodrigo Feitosa; Malcher, Paulo; Santos, Rodrigo Pereira dos (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2024: Anais do XXIII Simpósio Brasileiro de Qualidade de Software, 2024)
Requirements Engineering (RE) requires the collaboration of diverse stakeholders, including requirements engineers, end-users, and developers. Therefore, it is inherently a human-centric process. Identifying solutions for social and human factors (SHF) can contribute to RE activities. This study aims to identify solutions to deal with SHF to enhance RE activities. We conducted a rapid review, supplemented with the snowballing technique. At the end, 1,017 studies were retrieved, from which 46 were selected and analyzed to answer three research questions that provided us with an understanding of the existing solutions. Results indicate that such solutions encompass methods/techniques, models, practices, tools, theories, and frameworks. Furthermore, several solutions are specifically developed for requirements elicitation. Regarding the implications for academia, researchers can find an overview of the solutions proposed in the literature to address SHF in RE. For the industry, we mapped solutions with traceability to the SHF that they address.